An empirical study on barriers of innovation in indian smes - S, Poornima; K, Nithya Kala (Journal of Management and Science, 2012)
Small and Medium Enterprises (SMEs) have emerged as the drivers of growth in several developed and developing economies across the world. Innovation has become the vital factor for the growth of small and medium scale enterprises. Hence, Innovation has turned out to be nucleus issue of various studies all over the world. In today‘s competitive world, India is far behind in innovation. The slow growth of innovation across various manufacturing sectors in India is cited as root cause for business failures in turbulent business environment. This paper aims at highlighting the barriers faced by entrepreneurs in SMEs in India. This study further makes sector wise analysis and suggests policy measures to enhance the adoption of innovation in SMEs. This study would serve as a guide to the entrepreneurs to compete internationally.